The Kodiak Study: Narratives of Diversity and Acceptance on the American Frontier - Drewry, Steve (NSUWorks, 2014)
This article describes a qualitative study of diversity and acceptance on the American frontier comprised of interview data and ethnographic observations gleaned from a sample of residents on Kodiak Island, Alaska. Convenience and snowball sampling methods were used to select the study population, after which individual interviews with people who are members of various cultural groups were completed by the researcher. Also included in the study are elements of anthropological investigation, historical context and thick description. The data were analyzed using (primarily) narrative and thematic analysis placed in the cultural context of life on Kodiak Island. Findings suggest that multiple cultures can peacefully co-exist, and in fact co-create, a social milieu that is greater than the sum of its parts while maintaining independent cultural integrity.